A review of stevia as a potential healthcare product: Up-to-date functional characteristics, administrative standards and engineering techniques. (September 2020) - Wang, Junyan; Zhao, Hongli; Wang, Yueming; Lau, Hoching; Zhou, Wenhu; Chen, Chuanpin; Tan, Songwen
Abstract: Background: As a sugar substitute, stevia has attracted increasing attention because of reduced calories and natural origin. Recent studies have showed that stevia has numerous healthcare properties. Scope and approach: The importance of good practices for stevia used in foodstuffs is described as both a potential healthcare product and a sweetener. Based on recent reports, this work reviews the health-related characteristics from positive and negative sides, the current administrative standards for stevia-containing products, and the engineering techniques. Key Findings and Conclusions: Stevia demonstrates therapeutic benefits as a joint nutraceutical in the management of chronic diseases including overweight and obesity, diabetes mellitus, fatty liver, cardiac fibrosis, liver fibrosis, inflammatory bowel disease, certain types of cancer, hypertension, and chronic kidney diseases. Adverse effects mainly involve disorders of human metabolism and intestinal microbiota, genotoxicity, chronic toxicity, carcinogenicity, hypersensitivity, allergenicity and so forth. Although debate exists, the results obtained from current studies are in favour of recognizing stevia as a recommended substitute to sugar without obvious potential adverse effects on metabolic health. Based on daily safe intake levels of 4.0–4.4 mg/kg (as steviol equivalent), many countries have released administrative standards for the use of stevia in foodstuffs. The state-of-the-art production techniques are introduced from harvest, dehydration, grinding, extraction, purification and drying aspects. The future trends of research contain finding new healthcare properties and side effects, designing stevia-containing products (for improved taste) and improving engineering techniques. Graphical abstract: Image 1 Highlights: Stevia is a potential healthcare product. Stevia demonstrated therapeutic benefits of chronic diseases. Stevia has no obvious adverse effects on metabolic health. There is an increasing trend for stevia to be used in foodstuffs. Novel engineering techniques are required for stevia processing.